The factors that influence Liquefied Petroleum Gas (LPG) sales performance / Syarifah Nurul Ain Syed Ibrahim - Syed Ibrahim, Syarifah Nurul Ain (2011)
The availability of LPG as the multi-purpose fuel presents significant opportunities for extending energy services into the community and for generating value-added commercial and industrial applications. The developments of this energy sources can improve the economy besides the communities. As a multinational company who is generates and supplies the oil and gas sources, PETRONAS Dagangan Berhad (PDB) which is partly owned by the Petroleum Nasional (PETRONAS) played the roles in managing the oil and gas industry. This is done by getting information at PETRONAS Dagangan Berhad (PDB) itself by using secondary data that are related with the sales of LPG. The study covered the data from 2002 until 2010. The purpose of this study is to observe whether the gross national income (GNI), industrial production index (IPI) and the advertisement values can give impact to the LPG’s sales performance at the PDB’s Eastern Regional Office. Regarding the finding of the study, it shows that only two independent variables that have significant values which influenced the sales performance of liquefied petroleum gas. This study used the secondary data which obtained from PETRONAS Dagangan Berhad Eastern Regional Office as for the research methodology. Otherwise, the study used the Statistical Procedure of Social System to transform the data into the output to be analyzed. To conclude, the study found that the sales performance of LPG can be influenced by the industrial production index and the advertisement values